2012
DOI: 10.1152/ajpendo.00289.2012
|View full text |Cite
|
Sign up to set email alerts
|

Opposite-sex housing reactivates the declining GnRH system in aged transgenic male mice with FGF signaling deficiency

Abstract: Rochester JR, Chung WC, Hayes TB, Tsai PS. Opposite-sex housing reactivates the declining GnRH system in aged transgenic male mice with FGF signaling deficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 63 publications
1
9
0
Order By: Relevance
“…GnRH neurons respond to endogenous Kp concomitantly with their morphological remodeling 15 , however, the functional link between these two events has not been previously explored. To date, complex GnRH dendritic morphology was reported in only one mouse model exhibiting delayed puberty and fertility defects 23 , yet the functional relevance of the immature GnRH morphologies was not explored 23 . In our study, we found an increase of complex/immature GnRH dendritic morphology in the OVLT in nes::cre;Dmxl2 wt/loxp mice, associated with a decrease of unipolar morphology, and no changes in the bipolar GnRH dendritic morphology.…”
Section: Discussionmentioning
confidence: 99%
“…GnRH neurons respond to endogenous Kp concomitantly with their morphological remodeling 15 , however, the functional link between these two events has not been previously explored. To date, complex GnRH dendritic morphology was reported in only one mouse model exhibiting delayed puberty and fertility defects 23 , yet the functional relevance of the immature GnRH morphologies was not explored 23 . In our study, we found an increase of complex/immature GnRH dendritic morphology in the OVLT in nes::cre;Dmxl2 wt/loxp mice, associated with a decrease of unipolar morphology, and no changes in the bipolar GnRH dendritic morphology.…”
Section: Discussionmentioning
confidence: 99%
“…GnRH neurons are essential for epididymo-testicular descent and the onset and maintenance of sexual reproduction. Proper specification of GnRH cell fate, both prenatally and postnatally, relies on FGFs [ 11 ], and the developing GnRH system is highly sensitive to reduced levels of FGF signaling [ 12 ]. FGF-mediated signaling is involved in mitogenesis, proliferation, differentiation, cellular migration, angiogenesis, and tissue injury repair [ 13 ].…”
Section: Epididymo-testicular Descentmentioning
confidence: 99%
“…This is relevant for when considering reversible CHH as relatively few GnRH neurons are necessary for inducing pulsatile LH secretion (56). Further, murine studies suggest that the GnRH system is highly plastic as environmental stimuli such as sexual interactions can rescue GnRH function in some instances (57). Further, epigenetic influences seem also to play a critical role in the onset of puberty (58), and thus potentially in the reversal process.…”
Section: Etiology Of Chh Reversalmentioning
confidence: 99%